Aplikasi “W-Triangle” Efektif Meningkatkan Pengetahuan Underwear Rules Pada Anak Usia Sekolah - Sari, Maya; Fauziah, Munaya; Sutini, Titin; Anita, Apriliawati; Purnawati, Tri (Universitas Malahayati, 2024)
ABSTRACT School age children are children aged 7 - 12 years who are at a stage of development both cognitively, physically, morally and socio-emotionally. This stage begins with the child's entry into the school environment and the child's relationships with other people. According to KPAI data, the highest cases of sexual violence in 2021 were recorded including 536 cases of sexual abuse (62%), 285 cases of rape/coitus, 29 cases of same-sex sexual abuse (3%), 9 cases of same-sex sexual intercourse (1%). ). Providing educational education is facilitated with the help of media that makes understanding easier, including text (booklets), images (posters), sound (radio), audio visuals (video), other media can be objects such as mock ups. One of them uses device technology in the form of an application. The aim of this research is to determine the difference in the influence of education using digital booklet media and the